Economics - Krugman, Paul.; Wells, Robin (New Delhi Worth Publishers, 2010)
The same unique voice that made Paul Krugman a widely read economist is evident on every page of E conomics . The product of the partnership of coauthors Krugman and Robin Wells, the book returns in a new edition. The new edition is informed and informative, solidly grounded in economic fundamentals yet focused on the realities of today's world and the lives of students. It maintains the signature Krugman/Wells story-driven approach while incorporating organizational changes, new content and features, and new media and supplements. Watch a video interview of Paul Krugman here.
Keywords: Economics -- Macroeconomics